Proposal for Remodeling the Sedimentation System of the CONCREPAL Material Breaker at Barranca, Costa Rica - Arguedas-Zumbado, Nazareth (2016)
Due to a change in environmental paradigm and the production increase, this document is a proposal for remodeling the CONCREPAL’s settler located in Barranca, Costa Rica. It is presented as an eco-efficient alternative that simultaneously enables compliance with current legislation on landfill and wastewater reuse. Initially, an environmental diagnosis of the characteristics and performance of the current sedimentation tank was made. Subsequently, the design of the proposed remodeling of the treatment system, incorporating the recirculation of treated water in the breaker material production process, was developed. Finally, a life-size settler model was created in a test environment in order to start measurements tests and determine the functionality; successfully, after all tests, positive results within the range allowed by national legislation on total suspended-solids concentration (40 ± 0.01 mg/l) were obtained. Thanks to the cost-benefit and environmental management analysis, a new settler system can be implemented with positive short and long term results for the company.